Mn3+/Mn4+ ion-doped carbon dots as fenton-like catalysts for fluorescence dual-signal detection of dopamine - Zhu, Peide; Zhao, Xuelin; Zhang, Yuqi; Liu, Yinping; Zhao, Ziyi; Yang, Ziji; Liu, Xinzhu; Zhang, Weiye; Guo, Zixuan; Wang, Xiao; Niu, Yingchun; Xu, Meng (Frontiers in Bioengineering and Biotechnology, 2022)
Carbon dots (CDs), a new zero-dimensional material, have ignited a revolution in the fields of sensing, bioimaging, and biomedicine. However, the difficulty of preparing CDs with Fenton-like catalytic properties has seriously hindered their application in oxidative/reductive biomolecules diagnosis and tumor therapy. Here, an innovative method was successfully established to synthesize Mn3+/Mn4+ ion-doped green fluorescent CDs with Fenton-like catalytic properties using manganese acetate as the manganese source. Specifically, the CDs prepared here were equipped with functional groups of -COOH, NH2, C=O, and Mn-O, offering the possibility to function as a fluorescence sensor. More importantly, the introduction of manganese acetate resulted in the preparation of CDs with Fenton-like catalytic properties, and the dual-response fluorescence detection of dopamine (DA) was realized with linear ranges of 100~275 nM and 325~525 nM, and the detection limits were 3 nM and 12 nM, respectively. In addition, due to the Fenton-like catalytic activity of Mn3+/Mn4+ ion-doped CDs, the cell viability of 143B cells decreased significantly with the increase of CDs content, which could be successfully used for the bioimaging of 143B cells.